Padrões de diversidade espaço-temporal da assembleia de peixes estuarinos da costa semiárida brasileira: efeitos da influência marinha em diferentes escalas - Pinto, Leonardo Mesquita (2023)
Estuaries are transitional ecosystems and their functioning is conditioned by marine and freshwater influences. The balance of interaction between these two environments results in great dynamism in time and space. This buoyancy is considered to be the main aspect that shapes the assemblages of estuarine organisms. Alpha and beta taxonomic diversity indices describe community structure and provide answers about the ecological processes that structure assemblages. Adding the functional dimension in diversity analyzes allows the incorporation of attributes that directly influence the functioning of ecosystems, offering a complementary perspective to conventional taxonomic approaches. The present work investigates how different environmental conditions influence the patterns of taxonomic and spatiotemporal functional diversity of estuarine fish assemblages. In Chapter 1, six estuaries of the Brazilian Semi-Arid Coast with different levels of marine influence were sampled: Aracatimirim, Aracatiçu, Curu, Pacoti, Malcozinhado and Choró. The hypothesis of this chapter is that the level of marine influence at the estuary level has an effect on the spatio-temporal composition and beta diversity of fish assemblages. The results showed a significant effect of marine influence on composition and diversity patterns, with greater magnitude in the taxonomic dimension. Estuaries with a higher level of marine influence have lower temporal beta diversity values, conditioned by a more stable environment over time. The results of this study demonstrate the possible effects that marinization processes can have on patterns of spatiotemporal diversity of estuarine fish assemblages in semi-arid zones. Chapter 2 focuses on a more refined scale of analysis, intraestuarine, and aims to assess how diversity patterns are influenced by distance from the adjacent sea. An approach with composition data, alpha (spatial) and beta (temporal) diversity indices was used. The relationship between the distance from the adjacent sea and the two facets of diversity (alpha and beta) is expected to be opposite. Points closer to the sea would have greater α-diversity due to more favorable environmental variables and proximity to the pool of marine species. On the other hand, points farther from the sea would present greater β-diversity due to greater temporal variability in their environmental conditions. For this purpose, abiotic variables and fish assemblage were sampled in two estuaries of the Brazilian Semi-Arid Coast. Contrary to expectations, α-diversity was higher at points farther from the sea, possibly due to more favorable conditions for the colonization and survival of juvenile fish, which represent most of the studied assemblage. Temporal β-diversity was higher at points further upstream, but this effect was only detected in the taxonomic dimension. This study highlights the importance of the innermost estuarine zones for the generation and maintenance of fish biodiversity and the functioning of estuarine ecosystems in the semi-arid region. Considering the environmental factors that lead to changes in the patterns of spatiotemporal diversity of estuarine fish is essential to plan conservation actions for the ichthyofauna.